2000
DOI: 10.1161/01.cir.102.20.2484
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Management and Outcome After Acute Myocardial Infarction in the 1990s

Abstract: This prospective nationwide observational community-based study of consecutive AMI patients hospitalized in the CCUs in the mid 1990s indicates that women fare significantly worse than do men at 30 days but not thereafter at 1-year. The difference in 30-day outcome was not influenced by the use of different therapeutic modalities, including thrombolysis and invasive coronary procedures, but was rather due to the older age and greater comorbidity of women; these findings seem also to explain the less frequent u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
72
4
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(92 citation statements)
references
References 32 publications
9
72
4
6
Order By: Relevance
“…Momenuzzaman 7 did not observe any sex differential in terms of diabetes mellitus, while Hanratty et al 11 found a low prevalence of diabetes mellitus in both sexes (female 16%vs male 11%).Regarding hypertension, no significant difference was observed between the groups (female 42%, male 39%, p=0.666) bearing consistency with findings of Momenuzzma 7 . However, the findings differ from those reported by Gottlieb et al 9 and Jiang et al 10 who found a significantly higher prevalence of hypertension in females compared to males.Females had a higher incidence of hyperlipidemia as opposed to males (45% vs 32%, p=0.040). Similar results were also reported by others.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…Momenuzzaman 7 did not observe any sex differential in terms of diabetes mellitus, while Hanratty et al 11 found a low prevalence of diabetes mellitus in both sexes (female 16%vs male 11%).Regarding hypertension, no significant difference was observed between the groups (female 42%, male 39%, p=0.666) bearing consistency with findings of Momenuzzma 7 . However, the findings differ from those reported by Gottlieb et al 9 and Jiang et al 10 who found a significantly higher prevalence of hypertension in females compared to males.Females had a higher incidence of hyperlipidemia as opposed to males (45% vs 32%, p=0.040). Similar results were also reported by others.…”
Section: Discussioncontrasting
confidence: 87%
“…Similar smoking behaviour was observed in the studies conducted by others. 7,9,10 Diabetes mellitus was considerably higher in female patients (39%) than that in male patients (24%) which is consistent with Gottlieb et al 9 and Jiang et al 10 . Momenuzzaman 7 did not observe any sex differential in terms of diabetes mellitus, while Hanratty et al 11 found a low prevalence of diabetes mellitus in both sexes (female 16%vs male 11%).Regarding hypertension, no significant difference was observed between the groups (female 42%, male 39%, p=0.666) bearing consistency with findings of Momenuzzma 7 .…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…However in this study, the strongest predictors of not receiving reperfusion therapy were advanced age, delayed presentation, high systolic blood pressure and geographic region (South Africa). Previous studies have shown that women are less likely to be considered for reperfusion therapy than men, in some cases even after adjusting for important clinical differences [17][18][19]. Despite the higher mortality rates in women, fewer women may receive major diagnostic and therapeutic procedures than men [20][21][22], even though women treated with early aggressive revascularization procedures may have a better long-term outcome than that of men [23].…”
Section: Discussionmentioning
confidence: 99%